The use of oxygen microelectrodes to determine the net production by an Antarctic sea ice algal community - McMinn, A; Ashworth, CM (Antarctic Science, 1998)
Oxygen microelectrodes were used to measure the photosynthetic rates of Antarctic fast ice algal mats. Using the oxygen flux across the diffusive boundary layer below the fast ice at Davis, a productivity range of 0-1.78 mg C m-2 h-1 was measured. This is at the lower end of fast ice productivity estimates and suggests that conventional 14C techniques may overestimate sea ice algal mat productivity. Photosynthetic capacity (Pa(max)) approached 0.05 mg C. (mg chl a)-1 h-1. Onset of photosynthesis saturation, E(k), was found at c. 14 mol photons m-2 s-1. The irradiance of photoinhibition onset, E(inh), was c: 20 mol photons m-2 and the irradiance at the compensation point, E(c), was 4 mol photons m-2 s-1.